Efficacy and safety of asunercept, a CD95L-selective inhibitor, in hospitalised patients with moderate-to-severe COVID-19: ASUNCTIS, a multicentre, randomised, open-label, controlled, phase 2 trial - Ruiz Seco, Maria Pilar; Paño Pardo, José Ramón; Schoergenhofer, Christian; Dings, Christiane; Lehr, Thorsten; Herth, Felix; Krendyukov, Andriy; Straub, Carola; Kappler, Martin; Jilma, Bernd; Fricke, Harald; Pardo, Julian; et al. (EClinicalMedicine, 2024)
Background - The phase 2 ASUNCTIS study assessed the efficacy and safety of asunercept, a fully human CD95 (Fas) ligand-binding protein, in hospitalised patients with moderate-to-severe coronavirus disease (COVID-19) to assess the clinical benefit of CD95 ligand inhibition in this viral disease. - Methods - In this open-label, multicentre, randomised, controlled, phase 2 trial, patients with COVID-19-induced pneumonia and respiratory deterioration were randomly assigned (1:1:1:1) in 12 Russian and Spanish hospitals using an interactive web-response system to receive standard of care (SOC) or SOC plus weekly asunercept 25 mg, 100 mg, or 400 mg, administered intravenously for up to 4 weeks, or until hospital discharge or death. The randomisation was stratified according to the respiratory support methods at the time of enrolment, corresponding to categories 4-6 of a clinical severity assessment scale comprising 9 levels that was recommended by the World Health Organization (WHO) at the time of the study. The main inclusion criterion was laboratory confirmed infection with SARS-CoV-2 or typical radiological signs of SARS-CoV-2 infection. The primary endpoint was time from randomisation to clinical improvement on two consecutive days of at least one category on a WHO clinical severity assessment scale in the modified intent-to-treat population. All patients were subjected to regular safety analyses. This trial is registered with EudraCT (2020-001887-27) and ClinicalTrials.gov (NCT04535674). - Findings - Between October 9, 2020, and September 24, 2021, 438 patients were randomly assigned to SOC (n = 110) or SOC plus asunercept 25 mg (n = 109), 100 mg (n = 109), or 400 mg (n = 110). The primary endpoint, time to sustained clinical improvement of one WHO category on two consecutive days from randomization, was in median [95% confidence interval]: 9 [6-12], 8 [7-12], 8 [7-11] and 13 [9-20] days for the 400 mg, 100 mg, 25 mg asunercept and SOC groups, respectively. The standard deviations for the 400 mg, 100 mg, 25 mg asunercept and SOC groups were 5.3, 4.9, 4.7 and 5 days, respectively. The observed differences between groups failed to reach statistical significance (one-sided p-value = 0.041). In total, 290 adverse events (AE) were registered in 145 patients who received at least one dose of the study treatment: 77 AEs in 37 (33.6%) patients in the SOC group, 80 AEs in 38 (34.9%) patients in the 25 mg group, 61 AEs in 35 (32.7%) patients in the 100 mg group and 72 AEs in 35 (32.1%) patients in the 400 mg group. There was no treatment-related death reported. In summary, asunercept was well tolerated at all doses tested and no specific safety signals were detected. - Interpretation - The primary endpoint of time to sustained clinical improvement for distinct asunercept arms compared to SOC failed to meet statistical significance. The compound was safe and well tolerated. - Funding - Apogenix GmbH, Heidelberg, Germany.
Online verfügbar: 24. Oktober 2024
Gesehen am 23.01.2025